The gravity model in international trade - Salvatici, Luca (International Food Policy Research Institute, 2012)
Since Jan Tinbergen’s original formulation (Tinbergen 1962), gravity has long been one of the most successful empirical models in economics. Incorporating the theoretical foundations of gravity into recent practice has led to a richer and more accurate estimation and interpretation of the spatial relations described by gravity. Recent developments are reviewed here and suggestions are made for promising future research.